SPECIFIC FEATURES ASSOCIATED WITH THE IMAGE OF THE BRIDE IN "YOR-YOR"SONGS - Aliqulova Hulkar Qahramonovna (Galaxy International Interdisciplinary Research Journal, 2021)
The article discusses the peculiarities of the system of images in the songs performed at weddings, especially the popular expression in the description of the image of the bride, as well as national customs, rituals, thoughts, views on social life, as well as some magical features related to the expression of hair, veil, and colors in the songs are analyzed.